Research Trends on Health Education by Indonesia Researcher in Scopus Database: A Bibliometric Analysis (1996-2026) - Qorri Azizah; Zafrullah Zafrullah; James Leonard Mwakapemba; Rahayu Nurfadilla; Joy Cantika; Ghaitsa Shofa Rahmahdani (Penerbit Hellow Pustaka, 2026)
Health education plays a crucial role in improving knowledge, attitudes, and behaviors through educational processes. As attention to health-related issues in Indonesia continues to increase, research on health education has also grown substantially. However, no bibliometric study has comprehensively mapped the development of health education research in Indonesia. This study aimed to analyze publication trends, research focus, and keyword novelty in Indonesian health education research using a bibliometric approach. Data were retrieved from the Scopus database by limiting publications to those authored by researchers affiliated with Indonesian institutions. The article selection process followed the PRISMA guidelines, resulting in 225 eligible articles for analysis. The bibliometric analysis was conducted using the R Program to examine publication trends and VOSviewer to visualize research focus through keyword co-occurrence analysis and identify keyword novelty using overlay visualization. The results showed that publication output increased consistently from 2018 and reached its highest level in 2025. Keyword co-occurrence analysis identified five major research themes representing the diverse scope of health education research in Indonesia. Furthermore, the keywords children and reproductive health emerged as relatively recent topics, indicating promising directions for future research. These findings provide a comprehensive overview of the development of health education research in Indonesia and offer valuable insights for researchers, educators, and policymakers in establishing future research priorities and advancing evidence-based health education practices.